Case report: Repeat coronary function testing in women with ischemia and no obstructive coronary artery disease - Suppogu, Nissi; Tjoe, Benita; Wei, Janet; Maughan, Jenna; Joung, Sandy; Quesada, Odayme; Shufelt, Chrisandra L.; Samuels, Bruce; Azarbal, Babak; Bairey Merz, C. Noel (Frontiers in Cardiovascular Medicine, 2023)
Women with signs and symptoms of ischemia and no obstructive coronary artery disease (INOCA) often have coronary microvascular dysfunction (CMD). It can be diagnosed by coronary function testing (CFT), which is an invasive coronary angiogram procedure. Frequently, these women have persistent angina despite medical therapy, but it is not clear whether it is due to worsening or persistent CMD or inadequate therapy. In this brief report, we describe findings of repeat CFT in a case series of 12 women undergoing repeat CFT for the assessment of persistent angina in order to better understand the evolving pathology.